A new fractal watermarking method for images of text. (2019) - Kiani, Kourosh; Mousavi, Arash; Shamshirband, Shahaboddin
A new method, using the orthogonal fractal coding is developed for fractal watermarking of high contrast, low-density images of texts. In this method, image is divided into one pixel height sub-images. Each sub-image is coded separately using the orthogonal fractal coding technique. A binary watermark is re-ordered using a chaotic sequence. The binary watermark is inserted into the range block means of fractal codes. This fractal code is further decoded to obtain the watermarked image. The watermark sequence is retrieved by comparing the original image and the watermarked code. The extracted watermark is re-ordered using the key of the chaotic sequence. The method is robust against JPEG and noise attacks and has a very low watermark visibility.